Molecular Typing of Clostridium perfringens from a Food-Borne Disease Outbreak in a Nursing Home: Ribotyping versus Pulsed-Field Gel Electrophoresis - Schalch, Barbara (American Society for Microbiology, 2003)
In 1998, 21 inhabitants of a German nursing home fell ill with acute gastroenteritis after consumption of minced beef heart (P. Graf and L. Bader, Epidemiol. Bull. 41:327-329, 2000). Two residents died during hospital treatment. Seventeen Clostridium perfringens strains were collected from two different dishes and from patients' stool samples and autopsy materials. A majority of these isolates was not typeable by restriction fragment length polymorphism-pulsed-field gel electrophoresis (PFGE). Subsequent ribotyping of C. perfringens distinguished four different groups. The same ribopattern was detected in a minced beef heart dish, in autopsy material from the two deceased patients, and additionally in stool samples from six further residents who had fallen ill with diarrhea. Three further ribopatterns from food and autopsy materials could be differentiated. As chromosomal macrorestriction with subsequent PFGE is generally regarded more useful than ribotyping for molecular strain analysis, four selected isolates were lysed in parallel with a standard protocol and two nucleases inhibiting modifications. Neither of these methods could differentiate all of the isolates. These results suggest that PFGE with the current standard protocols is not able to characterize all C. perfringens isolates from food-borne disease investigations and that ribotyping is still a helpful method for molecular identification of clonal relationships.